Supplementary file 1_Twice-exceptional students: a systematic review to outline the distinctive characteristics through a multidimensional lens.docx - Ludovica Rizzo (22687391) (2025)
Introduction Twice-exceptionality can be described as a complex interaction between giftedness and one or more co-occurring challenges. Existing literature indicates that this coexistence may result in the inhibition of some characteristics typically associated with each condition when considered in isolation, the exacerbation of others, or the identification of new traits. However, limited data are available on this complex interplay, due to the small number of empirical studies conducted in this field, the difficulty in recruiting large samples, and the heterogeneous nature of the profiles investigated. This systematic review aims to identify the distinguishing characteristics of twice-exceptionality emerging from empirical studies conducted between January 2013 and January 2025. Methods Qualitative, quantitative, and mixed-methods studies were included and analyzed within a convergent integrated framework. Data were coded using MAXQDA software and thematically organized into six domains of functioning. Results Findings revealed some significant differences between twice-exceptional students and control groups consisting of gifted peers, students with clinically diagnosed challenges, and typically developing students. In addition, some case studies confirmed persistent traits either associated with giftedness or with challenges that appear to endure despite their coexistence. Discussion The findings suggest the need to adopt a personalized approach that account for the dynamic interplay between high potential and challenges, supporting more accurate identification and effective intervention. Systematic review registration Identifier: CRD42024549363 https://www.crd.york.ac.uk/PROSPERO/view/CRD42024549363.